Composite Materials: Three‐Dimensional Compressible and Stretchable Conductive Composites (Adv. Mater. 5/2014). (February 2014) - Yu, You; Zeng, Jifang; Chen, Chaojian; Xie, Zhuang; Guo, Ruisheng; Liu, Zhilu; Zhou, Xuechang; Yang, Yong; Zheng, Zijian
<x xml:space="preserve">Abstract</x> On page 810 Z. J. Zheng and co‐workers demonstrate three‐dimensional (3D) conductive composites with remarkable flexibility, compressibility, and stretchability that are fabricated by solution deposition of thin metal coatings on chemically modified, macroscopically continuous 3D polyurethane sponges, followed by infiltration of the metallic sponges with polydimethyl siloxane. The conductive composites are used as interconnects for 3D circuits. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>